Cinética da remoção dos extrativos da madeira de Eucalyptus grandis durante polpação Kraft - Sarto, Camila [UNESP]; Sansigolo, Claudio Angeli [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2010)
Kinetics of the removal of Eucalyptus grandis wood extractives during Kraft pulping. The objective of this work was to study the kinetics of the removal of Eucalyptus grandis wood extractives during Kraft pulping. The pulping was done in steel tubular reactors using wood saw under the following conditions: active alkali = 14%, sulfidity = 25%; liquor-to-wood ratio = 10 L kg(-1) of dry wood; and temperatures of 130, 150, 160 and 180 C during 30, 60, 90, 120, 150 and 180 minutes. After pulping, analyses were conducted of the yield and extractives in residue (pulp and reject). Total extractives (ethyl alcohol-toluene (1:2), ethyl alcohol and hot water, respectively) and soluble extractives in acetone were analyzed. The results showed that most extractives are degraded in the first 30 minutes of the pulping process. It was observed that the removal occurs in two different stages: the first is rapid, where the majority of the extractives are removed, and the last is slow, where few extractives are removed.
Kinetics of the removal of Eucalyptus grandis wood extractives during Kraft pulping
Keywords: Eucalyptus grandis; extractives; Kraft pulping process